2022
DOI: 10.3390/jcm11226727
|View full text |Cite
|
Sign up to set email alerts
|

Deep Endometriosis and Infertility: What Is the Impact of Surgery?

Abstract: In women with deep endometriosis, the spontaneous fertility rate might range from 2 to 10%. The optimal management of these women is still an area of debate. Therefore, this review aims to explore the literature on the impact of deep endometriosis surgery on reproductive outcomes and pregnancy rates in women with and without prior infertility. A total of 392 articles were identified through database searching. Twenty-three studies were eligible to be included in the review. A total of 1548 women were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…Surgical intervention remains a cornerstone in the management of endometriosis-associated pain and infertility, particularly for patients unresponsive to hormonal therapy. However, the optimal timing and approach to surgery remain subjects of debate, especially regarding DIE in infertility management vs. medically assisted reproduction treatments [ 12 ]. Pain intensity appears independent of disease stage or extent, complicating treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical intervention remains a cornerstone in the management of endometriosis-associated pain and infertility, particularly for patients unresponsive to hormonal therapy. However, the optimal timing and approach to surgery remain subjects of debate, especially regarding DIE in infertility management vs. medically assisted reproduction treatments [ 12 ]. Pain intensity appears independent of disease stage or extent, complicating treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures should be undertaken to alleviate pain and enhance pregnancy rates. In the case of infertility, there is a lack of evidence about whether surgical management should be used as the first intervention or only in cases where medically assisted reproduction treatment (ART) has failed [ 12 , 13 ]. Pain intensity is not influenced by the stage or extent of the disease, or the appearance and location of endometriosis deposits [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early surgical treatment was once considered a feasible way to avoid progression to infertility. However, studies have reported that conception rates do not appear to improve significantly even after prior therapeutic surgery related to endometriosis, not to mention the irreversible damage that such surgery may cause to the women themselves [ 19 ]. Assisted reproductive technology is a well-established treatment with efficacy and success rates varying among individuals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além das vantagens mencionadas anteriormente, a laparoscopia apresenta menor custo em comparação com outras abordagens invasivas, menor tempo de recuperação e permanência hospitalar, menor taxa de complicações pós-operatórias, melhor resultado estético após o procedimento, melhora da dismenorreia e dispareunia, e há indícios de melhoria na taxa de gravidez espontânea e nascidos vivos. Existem também novas técnicas de abordagem, como laser de fibra de CO2 e energia de plasma, mas ambas as técnicas ainda necessitam de mais estudos que confirmem sua solidez e eficácia no tratamento (Bafort et al, 2020, Lee;Seul Ki Kim;Byung Chul Jee, 2020, Angelos Daniilidis et al, 2022Carolina;Patricia Dias Fernandes, 2022, Pašalić;Tambuwala;Altijana Hromić-Jahjefendić, 2023, Tassinari et al, 2023.…”
Section: Abordagem Cirúrgicaunclassified